53BP1 depletion causes PARP inhibitor resistance in ATM-deficient breast cancer cells. Issue 1 (December 2016) - Hong, Ruoxi; Ma, Fei; Zhang, Weimin; Yu, Xiying; Li, Qing; Luo, Yang; Zhu, Changjun; Jiang, Wei; Xu, Binghe
Abstract Background Mutations in DNA damage response factors BRCA1 and BRCA2 confer sensitivity to poly(ADP-ribose) polymerase (PARP) inhibitors in breast and ovarian cancers. BRCA1/BRCA2-defective tumors can exhibit resistance to PARP inhibitors via multiple mechanisms, one of which involves loss of 53BP1. Deficiency in the DNA damage response factor ataxia-telangiectasia mutated (ATM) can also sensitize tumors to PARP inhibitors, raising the question of whether the presence or absence of 53BP1 can predict sensitivity of ATM-deficient breast cancer to these inhibitors. Methods Cytotoxicity of PARP inhibitor and ATM inhibitor in breast cancer cell lines was assessed by MTS, colony formation and apoptosis assays. ShRNA lentiviral vectors were used to knockdown 53BP1 expression in breast cancer cell lines. Phospho-ATM and 53BP1 protein expressions were determined in human breast cancer tissues by immunohistochemistry (IHC). Results We show that inhibiting ATM increased cytotoxicity of PARP inhibitor in triple-negative and non-triple-negative breast cancer cell lines, and depleting the cells of 53BP1 reduced this cytotoxicity. Inhibiting ATM abrogated homologous recombination induced by PARP inhibitor, and down-regulating 53BP1 partially reversed this effect. Further, overall survival was significantly better in triple-negative breast cancer patients with lower levels of phospho-ATM and tended to be better in patients with negative 53BP1. Conclusion These results suggest that 53BP1 may be a predictor of PARP inhibitor resistance in patients with ATM-deficient tumors.